Multiparametric evaluation of magnetic nanoparticles for theranostic applications in breast and pancreatic cancer - Crosbie-Staunton, Kieran (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2016)
Magnetic iron oxide nanoparticles (MNP) are superparamagnetic below 30 nm in size, have high surface to volume ratio in the nanometre size range, display no remnant magnetism in the absence of a magnetic field yet have high coercivity at high magnetisation and have high magnetic susceptibility. These beneficial properties favour the use of MNP in applications such as magnetic resonance imaging where they can be used as contrast agents, and in therapeutic applications such as magnetic-hyperthermia. In addition, the ability to coat the MNP with a range of surface modifying molecules provides further potential to functionalise the surface with targeting moieties and therapeutic agents such as chemotherapeutic drugs. Detecting cancers at an early stage not only increases the potential for complete removal of the diseased tissue, such as the lumpectomy of breast cancers, but also increases survival rate in diseases such as pancreatic cancer, where symptomatic presentation occurs mostly at the late stage of disease progression. Current therapies involving chemotherapeutic drugs, radiotherapy regimens and surgical intervention are highly invasive and generate undesirable side effects. The advent of nanomedicines has opened up a new avenue for potential detection and therapeutic applications. Through precise targeting of MNP via the incorporation of a surface bound targeting molecule specific for the diseased tissue, and the controlled release of chemotherapy drug at the site of the tumour, the systemic exposure to the chemotherapy drug can be dramatically reduced or completely eliminated, thereby preventing the associated side effects. In addition, the systemic dose delivered can be substantially lowered while maintaining the therapeutic dose delivered to the tumour bed. Furthermore, through exploiting the magnetic properties of the MNP, their in vivo biodistribution can be determined via imaging applications such as magnetic resonance imaging and in situ hyperthermia can be conducted in order to kill the cancer cells via thermal ablation. Therefore MNP could provide both a diagnostic and therapeutic modality for the detection and treatment of cancers at an early stage. In this study, a three-tiered safe-by-design characterisation approach was employed to facilitate the selection of a theranostic MNP. Characterisation steps included physicochemical characterisation (PCC), in vitro cytotoxicity, determination of in vitro anticancer efficacy, and in vivo biodistribution of seven MNP as part of the European Commission FP-7 project of Multifun. MNP synthesized by co-precipitation in water or by thermal decomposition were characterised by nanoparticle tracking analysis (NTA) and compared with characterisation conducted by Multifun partners in IMDEA, Madrid, Spain, using transmission electron microscopy (TEM) and dynamic light scattering (DLS). MNP High content screening analysis (HCSA) in four breast cancer cell lines (MCF-7, MDA-MB-231, BT-474 and SK-BR-3) and a normal-like breast-derived cell line (MCF-10A) was conducted to identify non-cytotoxic formulations. Lysosomal uptake was determined using LysoTracker® stained cells and bright field overlay to confirm localization of MNP following 24h exposure, which was confirmed as active uptake into lysosomes via clathrin-mediated endocytosis and micropinocytosis by partners in IMDEA, Madrid, Spain. Two biocompatible MNP were identified, OD15 and MF66. In vivo biodistribution and biocompatibility testing of MF66 MNP using a 7T magnetic resonance imaging device found that reliable detection of the MNP in the mouse was possible with imaging conducted at 4h post-injection. MNP uptake into mouse liver, spleen, lung, kidney, heart and brain was analysed by pEPR and blood circulation half-life was determined in a rat model. Furthermore, three linkers to facilitate functionalization onto OD15 and MF66 MNP were screened by HCSA for the ability to release an active drug compound (doxorubicin hydrochloride) and induce an anticancer effect. In addition, OD15 and MF66 were functionalized with the Nucant (N6L) pseudopeptide which, despite being cytotoxic in free form, enabled enhanced uptake of nanoparticles into cells. Multifunctionalised formulations including the N6L targeting moiety and gemcitabine hydrochloride chemotherapy drug were shown to have higher uptake into cells compared to non-targeted formulations and anticancer efficacy of both non-targeted and targeted formulations was similar to drug alone. Further in vitro evaluation demonstrated mitochondrial toxicity following exposure to drug-functionalised MNP which was associated with an increase in cell death by apoptotic or necrotic pathways. Evaluation of genotoxic potential by the OECD guideline (test 487) cytokinesis block micronucleus assay demonstrated that the MNP formulations did not induce chromosomal aberration compared to colchicine, a known micronucleus inducing compound. Therefore, this study enabled the identification and elimination of cytotoxic MNP formulations and facilitated the selection of the most suitable lead drug-functionalised MNP through systematic selection following a three-tiered safe-by-design approach.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin